A Retrospective comparative Study of Endoscopic and Microscopic Tympanoplasty - Tahir Rasheed, Aamer Ayub, Maqsood Ahmed, Uzair Hassan, Hassan Naeem, Muhammad Salman Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the outcomes of endoscopic vs. microscopic technique to tympanoplasty among patients. Methods: It was a retrospective study in which outcomes of sixty one ears of sixty patients (thirty three male and twenty seven female) who experienced type-1 tympanoplasty were assessed. Patients age range was between 20-50 years. Patients in Group-1 experienced tympanoplasty together with endoscopic procedure (n=32) while patients in Group-2 experienced tympanoplasty along with conservative microscopic approach (n=29). Among both groups patients, a rebound-shaped temporalis fascia was utilized. The results were studied regarding surgery time, success rate of graft and hearing gain. Results: Among both groups patients, postop ABG (air-bone gap) was considerably less than preop air-bone gap. Insignificant differences were found between pre- and post-op air-bone gap values (in decibel) in either cohort. Among Group-1 patients, mean surgery time was considerably less than Group-2 patients (51.37 versus 67.03 minutes)2. Among patients, this procedure was more frequently performed during current years3,4. Conclusion: Among patients experiencing type-1 tympanoplasty, particularly if external acoustic meatus is narrow and anterior canal wall is protuberant, endoscopic technique seems to offer results equivalent to microscopic technique for TM entire visualization while lack of additional interventions needed to assess the ossicular system.